THE HISTOLOGICAL AND BIOCHEMICAL STUDY OF THE EFFECT OF PURE FLAX SEED LIGNIN ON THE MAMMARY GLAND IN FEMAL RABBITS - Sinaa Jaboori Al-Bazii; Wefak Jaboori Al-Bazii (Basrah Journal of Veterinary Research)
This study was carried out to investigate the effect that result from taking 40 mg /kg BW of purified lignan from the seed of flax Linum usitatissimum L. in the growth and development of mammary glands during virgin , pregnancy and lactating stages for 14 days. Thirty (30) rabbits were used in this experiment divided into six groups, two groups at maturity (virgin) stage, two groups at pregnancy stages and two groups at lactating stages (5 rabbitseach group). The following studies were decided: histological, histochemical, biochemical and hormonal studies for each group. Microscopic examination of mammary gland in the virgin rabbits that treated with pure flax lignan showed more growth in the size of lobules and alveoli. In pregnant, the treated groups showed more branching of alveoli with more flattened epithelium. In lactating treated group showed the lobules were expanded and contained more branching alveoli with discontinuous flattened epithelium. The PAS staining reaction of histological sections of mammary gland from treated groups and control were showed positive reactions in all groups. The biochemical studies showed a significant increase (p